The Impact of AI-Enhanced Digital Marketing Strategies on Consumers’ Purchase Intention for Lifestyle Products - Ali Ghufran; Waqar Ahmad (Cihan University-Erbil Journal of Humanities and Social Sciences)
The impact of Artificial intelligence (AI)-powered digital marketing practices on consumer purchase intention toward lifestyle goods is the focus of this research and aims at analyzing the mediating role of consumer motivation (CM) in the relationship between consumer attitude (CA) and purchase behavior (PB) toward lifestyle products. The study uses descriptive research design to understand CA, motivation, and PB. The study is based on 577 responses collected from Uttar Pradesh state (India). Structural equation modeling was carried out with the help of SmartPLS. Evidence shows a robust relationship between consumers’ attitude, motivation and PB, and an optimistic outlook on AI-driven marketing campaigns is likely to inspire more action, given the robust positive correlation between customer attitude and motivation. The study also emphasizes the importance of CM as a mediator in the relationship between CA and PB. It emphasizes the strategic tools for improving PB in the dynamic digital marketing landscape, which include cultivating a positive CA. The study contributes to the theory by highlighting CM as a critical mediator linking CA s to PB for lifestyle products, advancing understanding of the attitude-behavior relationship in consumer behavior models. Managerially, it underscores the importance of designing marketing strategies that enhance CM, such as personalized engagement, value-driven messaging, and emotional appeal. By fostering motivation, brands can effectively translate positive attitudes into stronger PB, driving sales and long-term consumer loyalty in the lifestyle segment.